(untitled) (Revista Contexto & Saúde, 2022)
Rheumatoid arthritis (RA) is a inflammatory, chronic disease, which can bring several consequences to the individual. Patients with RA can present several comorbidities that may influence the clinical evolution of RA. Objective: evaluate the association between comorbidities and the RA activity profile among patients attending a rheumatology clinic of a public university hospital. Methods: this is a cross-sectional study, which collected demographic, diseases, lifestyle habits and RA profile data from a representative sample of patients with RA attending the outpatient clinic. A descriptive analysis of these data was performed, as well as univariate and multivariate analyzes to evaluate factors associated with the DAS28 (Disease Activity Score 28). Results: two hundred and one patients were included, a female majority (85.6%; n = 172) was detected and the mean age was 60.3 ± 11.5. Seven patients (3.5%) were obese, 17 (8.5%) smokers, 106 (52.7%) hypertensive, 38 (18.9%) diabetic and 72 (35.8%) had dyslipidemia. A mean functional comorbidity index of 2.3 ± 1.19 were identified in the sample. Age equal or greater than 60 years (OR = 0.40, 95% CI 0.21-0.74) and be diabetic (OR = 2.96, 95% CI, 30-6,74) were statistically significantly associated with moderate or high DAS28. Conclusion: the presence of comorbidities was frequent among patients with RA. Furthermore, age equal to or greater than 60 years was negatively associated, and a diagnosis of diabetes mellitus (DM) positively associated with moderate to high disease activity according. The findings reinforce the need for DM monitoring among these patients, especially the younger ones.